Ready, set, go: Medical preparations for the Paris 2024 Paralympic Games - Snyders, C.; Derman, W.; Schwellnus, M. (Journal of Sport and Health Science, 2024)
In August 2024, over 4400 Paralympic athletes will gather in Paris for the Paralympic Summer Games—the pinnacle of every Paralympian's (Para athletes competing at the Paralympic Games) career to showcase their ability and skills. Their training, preparation, and effort in the years leading up to the Games are unparalleled. To achieve success, Paralympians specifically rely on a medical support team to achieve their goals. So, what is required of the medical support team to prepare Paralympians to get ready, set, and go to Paris 2024?